The Use Of Jigsaw Type Cooperative Learning Model On Algebraic Factorization - Tandililing, Pitriana; Ruamba, Marthinus Yohanes (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to describe the implementation of the Jigsaw cooperative learning model in teaching algebraic factorization to eighth-grade students at SMP Negeri 1 Depapre, Jayapura Regency. Using a descriptive qualitative approach, this research examines the improvement in students' understanding and skills through expert and home group-based learning. Data collection was conducted through written tests and observations, focusing on student activity and instructional implementation. The findings indicate that the Jigsaw model significantly enhances student learning outcomes, achieving average scores above the minimum competency standards, along with positive changes in aspects of cooperation, responsibility, and student attitudes. This model is recommended for broader application to improve the quality of mathematics instruction in junior high schools.